STUDENTS - TOP ATHLETES ABOUT DUAL CAREER - Kravalis, Ivars; Ābeļkalns, Ilvis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This article aims to give an overview of students – top athlete experience, how to combine studies at university with a sports career. For the data, the acquisition was used as an individual, written survey with mixed-type questions by form. Applicants of the survey were students who are in the national team or master players. The data from the survey was processed by AQUAD Seven, was used descriptive and inferring statistics analysis of factors using the data statistical processing programs SPSS and Excel. Talented athletes have to make an important choice about their future after graduating high school: to start studies at university, focus on sports careers or combine these two goals. Combining studies to the high-achievement sport is the goal of dual career, it is a serious step for every young talent. In this article, we summarise top athlete opinions, who are studying in Latvian universities, about dual-career. Their recommendations for improving the situation, expanding opportunities and engaging mentors in certain study programs they are studying in. Conclusions are drawn, that there is possible development in a dual career, based on the results of this and previous author`s researches. Different universities and programs have different possibilities and experiences in creating the study process for the top athletes, which should be taken into consideration when making a united dual-career model for universities.